2022
DOI: 10.15218/edj.2022.5
|View full text |Cite
|
Sign up to set email alerts
|

Vertical marginal gap evaluation of PEEK and Zirconia crowns using extra-oral scanner and CAD/CAM systems (An Invitro study).

Abstract: Results:The average (mean) for the marginal gap of proximal, buccal and lingual surfaces of both PEEK, and zirconia materials were: 409.097 μm, 112.869 μm, 198.563 μm, for PEEK and, 105.085 μm, 27.659 μm, 45.135 μm for zirconia respectively. Statistical analysis using t -test for two independent samples revealed that PEEK material showed a significantly higher marginal gap than z. irconia material. Conclusion:PEEK crowns had a higher marginal gap than clinically acceptable limit, while zirconia crowns exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Roy et al [ 41 ] reported the same conclusions in an in vivo experiment. Moreover, Aula RA et al [ 42 ] concluded that PEEK crowns had a marginal gap of 409.09 μm, 112.86 μm, and 198.56 μm for proximal, buccal and lingual surfaces, respectively, which is higher than the clinically acceptable limit, while zirconia crowns exhibited much lower measurements, 105.08 μm proximal, 27.65 μm buccal, and 45.13 μm lingual. The difference might be attributed to the variation in methodology, as they used 3-unit FDP, and the marginal gap was assessed using a stereomicroscope at 160X.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy et al [ 41 ] reported the same conclusions in an in vivo experiment. Moreover, Aula RA et al [ 42 ] concluded that PEEK crowns had a marginal gap of 409.09 μm, 112.86 μm, and 198.56 μm for proximal, buccal and lingual surfaces, respectively, which is higher than the clinically acceptable limit, while zirconia crowns exhibited much lower measurements, 105.08 μm proximal, 27.65 μm buccal, and 45.13 μm lingual. The difference might be attributed to the variation in methodology, as they used 3-unit FDP, and the marginal gap was assessed using a stereomicroscope at 160X.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these findings might be due to PEEK's semicrystalline structure, which includes fillers entrapped in a resin matrix yielding a greater marginal gap during manufacturing than zirconia, which has a polycrystalline structure [ 42 ].…”
Section: Discussionmentioning
confidence: 99%